Instruction flow mining algorithm based on the temporal sequence of node communication actions - Yingzhuo XIANG; Zhengguo XU; Ling YOU (Tongxin xuebao)
With the situation that the content of the communication between the nodes in the network is unknown,an instruction flow mining algorithm based on the communication sequence was proposed.Firstly,by modelling the relativity of the communication actions and proposing the node communication actions model,the background communication and instruction communication actions was modelled.Moreover,FlowMine algorithm was proposed to solve such models and the convergence of the algorithm was analyzed.The algorithm estimated parameters by sampling and iteration which obtained a near optimal solution.Finally,the validity of the approach was verified by synthetic data and empirical data analysis.Experiment results show the convergence and reliable performance of FlowMine algorithm.